Metafisica del Diritto e construzione die rapporti giuridici - Livi, Antonio (Categorialità e trascendentalità del diritto, 2007)
In the distinction between theoretical and constructive knowledge, philosphy shows ist vocation for bringing to light "things that are" (poietics), while Law, as ordinatio rationis, distinguishes itself by ist "constructive" vocation aiming at building working systems of human reality. Poietic and constructive doctrines differ from one another in their relationship with historicity: philosophy is, in itself, unhistorical, while Law belongs to the history which it wants to arrange